Analysis of Twisted Tall Structure Considering Lateral Load using ETABS - Md Afsar Alam; Reetesh Khare (International Journal of Scientific Research in Civil Engineering, 2022)
This examination presents the underlying way of behaving of RCC wound building exposed to dynamic burdens. The similar concentrate between RCC wound building is made. In a wound tall structure different pace of contort for RCC bent building was investigated. The different pace of bend as 10, 12.5 and 15 degrees at the focal point of the RCC wound building was thought of. The demonstrating and investigation is finished utilizing ETABS. Dead loads, live burden, seismic burden and wind loads are allocated for demonstrated designs and results acquired are plotted for boundaries, for example, removal, story float, time-frame and base shear. The investigation for turned building is finished gravity loads, horizontal burden utilizing Response range strategy. The models are considered for Zone V and the investigation is done according to the Indian standard codal arrangements. From the relative investigation of RCC working under Dynamic burdens for different point of bend for story it is reasoned that RCC wound building is proficient under seismic and wind load. 10 degree point of turn is effective contrasted with 12.5 and 15 level of point of bend.
Keywords: RCC Twisted Building; Steel Twisted Building; Base Shear; Time Period; Displacement & Storey Drift